An Empirical Research on Factors Affecting the Acceptance of Bitcoin in the Northern Region of Malaysia - Jaya Kumar Shanmugam; Barathy Doraisamy; Santhi Appannan; Parteeban Varatarajoo; Nurul Jannah Abdul Aziz (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this study is to identify the relationship between factors affecting the acceptance of Bitcoin in the Northern Region of Malaysia. Past studies with reference to the factors affecting the acceptance of Bitcoin were being done on a larger scale outside of Malaysia and none of the studies has narrowed it down to make the research more specific. Therefore, this study proposed to study the factors affecting the acceptance of Bitcoin in the Northern Region of Malaysia based on performance expectancy, risk, social influence, and facilitating conditions. Furthermore, the relationship between the factors affecting the acceptance of Bitcoin and the acceptance of Bitcoin in the Northern Region of Malaysia has been discovered in this research. The population selected for this exploration is the respondents in Perlis, Kedah, Pulau Pinang, and Perak. The primary data for this research has been collected from the respondents through an online survey questionnaire. The data collected is then analyzed using various data analysis methods such as descriptive analysis, Pearson Correlation Coefficient Analysis, and Multiple Linear Regression Analysis. Hypotheses testing have been done after the analysis has been analyzed. This study presents supplementary information to potential researchers who wish to study in-depth in this area. Moreover, the results of this study contribute to the users as they get to know what factors to consider when they want to use Bitcoin and it helps Bitcoin Trader Company in their decision-making processes to attract more users. Nevertheless, the factors affecting the acceptance of Bitcoin most efficiently are identified in this research. Therefore, the acceptance of Bitcoin in the Northern Region of Malaysia can be affected by performance expectancy, risk, social influence, and facilitating conditions factors.